Accelerating Net-Zero Emissions in Heavy Industry: an Integrated Framework for Sustainability Management Strategy, Implementation, and Performance Measurement - Abubakar, Al Asri; Halimah, Halimah (Jurnal Mamangan, 2023)
This study investigates the critical challenge of achieving net-zero emissions in Southeast Asian heavy industries, employing a mixed-method approach combining quantitative analysis of 300 companies and qualitative case studies of six organizations. We examine the efficacy of sustainability management strategies, implementation frameworks, and performance measurement systems in accelerating net-zero transitions. Our findings reveal that companies with structured implementation frameworks are 3.7 times more likely to achieve net-zero targets on schedule (p < 0.001), while robust performance measurement systems correlate with a 2.5-year acceleration in target achievement (β = -2.5, p < 0.01). We develop and validate a novel implementation framework and a tailored Balanced Scorecard for net-zero initiatives. This research contributes to the literature by proposing an integrated model linking sustainability strategy, implementation mechanisms, and performance outcomes in net-zero transitions. Our findings offer theoretical insights into organizational change dynamics and provide evidence- based tools for industry practitioners and policymakers in high-emission sectors